The Antiviral Potential of Iranian Herbal Pharmacopoeia (IHP) on Herpes Simplex Viruses (HSV): A Review Article - Shahin Gavanji (Biology, Medicine, & Natural Product Chemistry, 2022)
Herpes Simplex Viruses (HSV) viruses are highly contagious that commonly cause dermatitis, encephalitis, meningitis and genitourinary infections and also can lead to cervical cancer. For treatment of HSV infections, several physical methods and antiviral drugs are introduced, antiviral medications can also prevent or reduce outbreaks. The use of herbal medicine with antiviral effects attracted worldwide attentions. The aim of this review article is to introduce the Iranian Herbal Pharmacopoeia (IHP) with antiviral potential against two HSV serotypes and help to evaluate and develop the new drugs from natural sources. To provide this review, relevant articles in some authentic databases including PubMed, Web of Science, Science Direct, Scopus, Google Scholar and SID (scientific information database), from 1967 to April 2022 were collected, and selected botanicals from (IHP) with their scientific names and classifications and their outcome (CC50 and IC50) were introduced. In this review, scientific data regarding anti-herpetic activities of Iranian Herbal Pharmacopoeia (IHP) showed that 34 herbs from 17 families have antiviral potential to inhibit two HSV serotypes. According to families, Lamiaceae family has the highest percentage (29.41 %) of plants with antiviral activity against two HSV serotypes, also review of recent data showed that Salvia officinalis, Melissa officinalis, Securigera Securidaca, Hyssopus officinalis, Quercus brantii, Artemisia aucheri and Curcuma longa have remarkable antiviral activity against two HSV serotypes. Results of this review suggest that further research to identify and purify the bioactive compounds to determine the molecular mechanisms of action is needed.